The Narrators in whom the Sayings of the Critical Imams Differed, whether Distorted or Modified: A Comparative Critical Study (The International Journal for Scientific Research, 2024)
Praise be to God, and may blessings and peace be upon the Messenger of God and upon his family and all his companions, and after:This is a summary of the research entitled: “The narrators about whom the sayings of the critical imams differed, both in terms of distortion and modification,” a comparative critical study. The study aimed to find out what is most likely in judging the narrators about whom the sayings of the imams differed, “Abd al-Haqq al-Ishbili, Ibn al-Qattan al-Fasi, and his student Ibn al-Mawwaq,” in terms of distortion and modification.  I followed the method of induction and analysis in explaining the ranks of words, comparing with the critics’ sayings in judging the narrators, studying the extent of agreement and disagreement in them, and stating the most correct of them. I concluded that Al-Ishbili, then Ibn Al-Qattan, and Ibn Al-Mawaq are among the most famous figures of the Hadith school in Morocco, as they represent an extension of to its greatest scholars; This is due to their progress, extensive knowledge, and knowledge of the conditions of the narrators and the rulings of the critics, and their sources for their sayings from the approved books of the Sunnah. I recommend that the circle of interest be expanded in the knowledge of the sayings of the imams regarding the narrators, whether distorted or modified, and that they be studied in a critical and comparative study until one can reach a judgment on the narrator and know his class, for they are buried treasures that require a skilled diver. It is revealed, as this science is one of the most important sciences that develops understanding and strengthens the scientific personality of the researcher.
Keywords: Al-Jarh; Al-Ta'deel; Al-Ishbili; Ibn Al-Qattan; Ibn Al-Mawaq; unknown